Tunable energy harvesting vibration absorber with liquid-metal filled elastic chamber. (1st May 2023) - Guo, Moshan; Zheng, Gangtie
Abstract: This paper presents a novel tunable energy harvesting vibration absorber with liquid-metal filled elastic chamber (TEHVA-LMEC) for simultaneously achieving tuned energy harvesting and semi-active vibration suppression. This device consists of a rigid chamber covered with two rubber membranes, two parallel magnets, copper bar electrodes, and liquid metal filled inside the chamber. Liquid metal functions both as the core component for electromagnetic energy harvest, i.e. cutting the magnetic induction lines and producing electricity, and in the meantime provides inertia as liquid mass for vibration suppression. Therefore, TEHVA-LMEC inherits the advantages of both liquid-mass tuned vibration absorbers (TVAs) and electromagnetic energy harvesters, including weight efficiency, simpler tuning procedure, and larger power output with lower internal impedance. More importantly, the natural frequency and the optimal energy harvesting frequency of TEHVA-LMEC are adjusted synchronously, which is beneficial in engineering applications where external excitation and the primary structure's dynamic characteristics are not constant. A single-degree-of-freedom (SDOF) analytical model of TEHVA-LMEC is proposed for the discussions of its output voltage and natural frequency. A parameter investigation reveals that the rated output voltage can be designed by adjusting two design parameters. A prototype based on the analytical model is tested on an electrodynamic shaker. Experiments evaluated the electromagnetic energy harvesting function and its characteristic with different vibrating frequencies. Both tuned energy harvesting and vibration absorption functions of TEHVA-LMEC are verified.